905 How to prioritise patients and safely resume elective surgery during the Covid-19 pandemic. (4th May 2021) - Subbiah Ponniah, H; Ahmed, M; Edwards, T; Cobb, J; Dean, E; Clark, C; Logishetty, K
Abstract: Introduction: There are now over 2.5 million NHS patients awaiting elective surgery, with the most in orthopaedics. We present an algorithm and results for safely and equitably restarting surgery at COVID-light sites. Method: An MDT applied the COVID-19 Algorithm for Resuming Elective Surgery (CARES) on 1169 patients awaiting elective orthopaedic surgery. It assessed safety, procedural efficacy, and biopsychosocial factors, to prioritise patients. They were assigned to five categories and underwent surgery at one of three COVID-light sites (1. access to HDU/ITU/Paediatrics/specialist equipment, 2. an NHS elective surgical unit and 3. a private elective surgical unit). Results: 21 'Urgent' patients received expedited care; 118 were Level 1/2; 222 were Level 3; 808 were Level 4. In 6 weeks, 355 surgeries were performed, with Urgent and Level 1/2 cases performed soonest (mean 18 days, p < 0.001). 33 high-risk/complex/paediatric patients had surgery at Site 1 and the rest at Sites 2 and 3. No patients contracted COVID-19 within 2 weeks of surgery. Conclusions: We validated a widely generalisable model to facilitate resumption of elective surgery in COVID-light sites. It enabled surgery for patients in most suffering, undergoing the most efficacious procedures and/or at highest risk of deterioration, without compromising patient-safety.